Investigation of magnetically driven passage of magnetic nanoparticles through eye tissues for magnetic drug targeting - Zahn, Diana; Klein, Katja; Radon, Patricia; Berkov, Dmitry; Erokhin, Sergey; Nagel, Edgar; Eichhorn, Michael; Wiekhorst, Frank; Dutz, Silvio (Nanotechnology, 2020)
This paper elucidates the feasibility of magnetic drug targeting to the eye by using magnetic nanoparticles (MNPs) to which pharmaceutical drugs can be linked. Numerical simulations revealed that a magnetic field gradient of 20 T m-1 seems to be promising for dragging magnetic multicore nanoparticles of about 50 nm into the eye. Thus, a targeting magnet system made of superconducting magnets with a magnetic field gradient at the eye of about 20 T m-1 was simulated. For the proof-of-concept tissue experiments presented here the required magnetic field gradient of 20 T m-1 was realized by a permanent magnet array. MNPs with an optimized multicore structure were selected for this application by evaluating their stability against agglomeration of MNPs with different coatings in water for injections, physiological sodium chloride solution and biological media such as artificial tear fluid. From these investigations, starch turned out to be the most promising coating material because of its stability in saline fluids due to its steric stabilization mechanism. To evaluate the passage of MNPs through the sclera and cornea of the eye tissues of domestic pigs (Sus scrofa domesticus), a three-dimensionally printed setup consisting of two chambers (reservoir and target chamber) separated by the eye tissue was developed. With the permanent magnet array emulating the magnetic field gradient of the superconducting setup, experiments on magnetically driven transport of the MNPs from the reservoir chamber into the target chamber via the tissue were performed. The resulting concentration of MNPs in the target chamber was determined by means of quantitative magnetic particle spectroscopy. It was found that none of the tested particles passed the cornea, but starch-coated particles could pass the sclera at a rate of about 5 ng mm-2 within 24 h. These results open the door for future magnetic drug targeting to the eye.
CRIS-Team Scopus Importer:2020-10-16
Keywords: magnetic drug targeting; magnetic field gradient; magnetic nanoparticles; magnetic particle spectroscopy

In vitro effects of benzalkonium chloride and prostaglandins on human meibomian gland epithelial cells - Rath, Anca; Eichhorn, Michael; Traeger, Katharina; Paulsen, Friedrich; Hampel, Ulrike (Annals of Anatomy-Anatomischer Anzeiger, 2019)
Purpose: Benzalkonium chloride is the most widely used preservative in ophthalmic topical solutions. The aim of this study was to investigate the influence of BAC as a single substance or as a component of several commercially available ophthalmic solutions on meibomian gland epithelial cells in vitro.
CRIS-Team WoS Importer:2019-04-18